Nutraceutical properties of Thai - Chareonchai Jeamchanya; Chalerm Jansom; Chisanucha Sattaponpun; Pranee Nandhasri; Kammal Kumar Pawa; Jamnong Kaewtubtim (Songklanakarin Journal of Science and Technology (SJST), 2005)
Morinda citrifolia Linn. is known in Thailand as "Yor" and commonly called "Noni" in Hawaii, Tahiti and USA. This paper reports the results of chemical analysis of Thai "Yor" (M. citrifolia) juice extract. The juice from "Yor" fruit, was found to be high in vitamin C, vitamin B-complex contents (HPLC method), and was also high in anti-oxidants, anthraquinones, flavonoids, saponins and scopoletin (TLC method). Sodium, potassium, calcium, iron and selenium contents of the juice (AAS method) are also reported. All the results of Thai "yor" juice are comparable to those of the commercially distributed 'Noni' juice. The Thai "Yor" juice was free of microorganisms and could safely be consumed in the recommended amount of 30 ml/day. The results of this study only apply to the Thai "Yor" juice preparation. The commercial "Noni" juice may be processed differently and may contain other ingredients.